The influence of probing prompting learning model on junior high school critical thinking skills in science subjects - Jariatin, Nurul Hida; Putra, Pramudya Dwi Aristya; Wicaksono, Iwan (CAHAYA PENDIDIKAN, 2024)
TThe main problem in the world of education today is the low critical thinking skills of junior high school students in science subjects. This research aims to examine the influence of the probing prompting learning model on junior high school students' critical thinking skills in science subjects. The type of research is a quasi experiment with a nonequivalent control group design. The samples used were students in class VIII C (experimental class) and VIII B (control class). Sampling used purposive sampling technique. Data was obtained from pre-test and post-test question instruments. Data analysis techniques use normality test, independent sample t-test, and N-Gain test. Analysis of research results using SPSS version 25.0 obtained a significance value (2-tailed) > 0.05, which shows that the application of the probing prompting learning model has a positive effect on students' critical thinking skills in science subjects. The research results showed that the influence of the probing prompting learning model was able to improve critical thinking skills starting from high to low criteria including interpretation, self-regulation, explanation, conclusion, evaluation, analysis. The application of the probing prompting learning model is effective in improving students' critical thinking skills.